2017
DOI: 10.1080/02643294.2017.1299001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a differential interference of noise in sub-lexical and lexical reading routes in healthy participants and dyslexics

Abstract: The ineffective exclusion of surrounding noise has been proposed to underlie the reading deficits in developmental dyslexia. However, previous studies supporting this hypothesis focused on low-level visual tasks, providing only an indirect link of noise interference on reading processes. In this study, we investigated the effect of noise on regular, irregular, and pseudoword reading in 23 dyslexic children and 26 age- and IQ-matched controls, by applying the white noise displays typically used to validate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Developmental dyslexia (DD) is characterized by a reading impairment, despite normal intelligence and adequate reading instruction. Although phonological processing deficits are well established as core deficits in DD (Snowling, 1981;, it has been suggested that attentional impairments may also contribute to the pathophysiology of this condition (Cestnick and Coltheart, 1999;Vidyasagar, 1999Vidyasagar, , 2019Facoetti et al, 2005Facoetti et al, , 2006Vidyasagar and Pammer, 2010;Pina Rodrigues et al, 2017a types of attention deficits have been reported in DD: narrowed visual attentional window and reduced visual attention span ; stronger effects of crowding (Bouma and Legein, 1977;Spinelli et al, 2002;Pernet et al, 2006;Moores et al, 2011;Callens et al, 2013); noise exclusion deficits (Sperling et al, 2005(Sperling et al, , 2006Pina Rodrigues et al, 2017a); and, particularly relevant for this study, abnormal spatial distribution of attention (Facoetti and Turatto, 2000;Facoetti and Molteni, 2001) and impaired attention orienting (Brannan and Williams, 1987;Facoetti et al, 2000bFacoetti et al, , 2003aFacoetti et al, , 2006Facoetti and Molteni, 2001;Kinsey et al, 2004;Valdois et al, 2004;Roach and Hogben, 2008;Vidyasagar and Pammer, 2010;Franceschini et al, 2012;Gabrieli and Norton, 2012). Moreover, it has been shown that prereading visuo-attentional skills can predict reading impairments (Franceschini et al, 2012;Carroll et al, 2016;Valdois et al, 2019) and that attentional training is able to improve reading in dyslexics (Franceschini et al, 2013), suggesting a causal link between attention...…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dyslexia (DD) is characterized by a reading impairment, despite normal intelligence and adequate reading instruction. Although phonological processing deficits are well established as core deficits in DD (Snowling, 1981;, it has been suggested that attentional impairments may also contribute to the pathophysiology of this condition (Cestnick and Coltheart, 1999;Vidyasagar, 1999Vidyasagar, , 2019Facoetti et al, 2005Facoetti et al, , 2006Vidyasagar and Pammer, 2010;Pina Rodrigues et al, 2017a types of attention deficits have been reported in DD: narrowed visual attentional window and reduced visual attention span ; stronger effects of crowding (Bouma and Legein, 1977;Spinelli et al, 2002;Pernet et al, 2006;Moores et al, 2011;Callens et al, 2013); noise exclusion deficits (Sperling et al, 2005(Sperling et al, , 2006Pina Rodrigues et al, 2017a); and, particularly relevant for this study, abnormal spatial distribution of attention (Facoetti and Turatto, 2000;Facoetti and Molteni, 2001) and impaired attention orienting (Brannan and Williams, 1987;Facoetti et al, 2000bFacoetti et al, , 2003aFacoetti et al, , 2006Facoetti and Molteni, 2001;Kinsey et al, 2004;Valdois et al, 2004;Roach and Hogben, 2008;Vidyasagar and Pammer, 2010;Franceschini et al, 2012;Gabrieli and Norton, 2012). Moreover, it has been shown that prereading visuo-attentional skills can predict reading impairments (Franceschini et al, 2012;Carroll et al, 2016;Valdois et al, 2019) and that attentional training is able to improve reading in dyslexics (Franceschini et al, 2013), suggesting a causal link between attention...…”
Section: Introductionmentioning
confidence: 99%
“…Although phonological processing deficits are well established as core deficits in DD ( Snowling, 1981 ; Ziegler and Goswami, 2005 ), it has been suggested that attentional impairments may also contribute to the pathophysiology of this condition ( Cestnick and Coltheart, 1999 ; Vidyasagar, 1999 , 2019 ; Hari and Renvall, 2001 ; Facoetti et al, 2005 , 2006 ; Bosse et al, 2007 ; Vidyasagar and Pammer, 2010 ; Pina Rodrigues et al, 2017a ). Accordingly, several types of attention deficits have been reported in DD: narrowed visual attentional window and reduced visual attention span ( Bosse et al, 2007 ); stronger effects of crowding ( Bouma and Legein, 1977 ; Spinelli et al, 2002 ; Pernet et al, 2006 ; Martelli et al, 2009 ; Moores et al, 2011 ; Callens et al, 2013 ); noise exclusion deficits ( Sperling et al, 2005 , 2006 ; Pina Rodrigues et al, 2017a ); and, particularly relevant for this study, abnormal spatial distribution of attention ( Facoetti and Turatto, 2000 ; Facoetti and Molteni, 2001 ) and impaired attention orienting ( Brannan and Williams, 1987 ; Facoetti et al, 2000b , 2003a , 2006 ; Facoetti and Molteni, 2001 ; Hari and Renvall, 2001 ; Kinsey et al, 2004 ; Valdois et al, 2004 ; Roach and Hogben, 2008 ; Vidyasagar and Pammer, 2010 ; Franceschini et al, 2012 ; Gabrieli and Norton, 2012 ). Moreover, it has been shown that prereading visuo-attentional skills can predict reading impairments ( Franceschini et al, 2012 ; Carroll et al, 2016 ; Valdois et al, 2019 ) and that attentional training is able to improve reading in dyslexics ( Franceschini et al, 2013 ), suggesting a causal link between attentional deficits and reading impairments.…”
Section: Introductionmentioning
confidence: 99%